Lower starting dose of roxadustat in non-dialysis-dependent chronic kidney disease patients with anaemia: a study protocol for a randomised, multicentre, open-label study. Issue 2 (9th February 2023) - Li, Ping; Sun, Xuefeng; Chen, Dinghua; Lin, Hong-li; Zhang, Li; Wu, Yiqing; Pan, Shuting; Cai, Guangyan; Chen, Xiangmei
Abstract : Introduction: Roxadustat is a first-in-class oral therapy that treats chronic kidney disease (CKD) anaemia with the benefit of a novel mechanism of action that consistently corrects and maintains haemoglobin (Hb) across the spectrum of non-dialysis-dependent (NDD) CKD anaemia with an acceptable safety profile. Methods and analysis: This is a randomised, control, open-label, multicentre trial. About 250 adult Chinese participants with stage 3–5 CKD NDD in approximately 30 centres will be enrolled, randomly assigned in a 1:1 ratio, to receive a 16-week treatment and 4-week follow-up. The interventions for study arm are <60 kg: 50 mg TIW and ≥60 kg: 70 mg TIW; for control arm, <60 kg: 70 mg TIW and ≥60 kg: 100 mg TIW. The primary endpoint is the mean change in haemoglobin level from baseline to average over weeks 12–16. Secondary endpoints are to assess the proportion of subjects achieving an average Hb level of 100 to 120 g/L over weeks 12–16, the Hb variability, the rescue therapy requirement between two groups and the safety in two groups. The exploratory objectives are expected to evaluate the rate and time of Hb response, times of dose adjustment, the proportion of subjects with rapid Hb rise, overshooting during the treatment between two different starting dose groups, and subgroup analyses. Ethics and dissemination: The Medical Ethics Committee of Chinese PLA General Hospital has approved this study (No. S2020-523-05) and will be performed in accordance with the Declaration of Helsinki. Participant consent will be obtained in writing. Results will be disseminated via peer-reviewed publications and conference presentations. Trial registration number: ChiCTR2100045359.